A new map of ye north parts of America claimed by France under ye names of Louisiana, Mississippi, Canada & New France, with the adjoyning territories of England & Spain - Moll, Herman, d. 1732 ([London], 1736)
Hand coloured. Prime meridian London. North arrow. Relief shown pictorially. CNS map no. 1. Leaf no. in upper-right corner: 46.